ANALYSIS OF CAUSALITY OF THE FOREIGN DIRECT INVESTMENT WITH ECONOMIC GROWTH: APPLICATION OF TURKEY - Kendirli, Selçuk; Cankaya, Muhammet; Cagatay, Altug (PEOPLE: International Journal of Social Sciences, 2017)
There are a lot of factors, which ones affect to the growth of economy. According to some economists mention that one of those factors is the foreign direct investment. In this study we examined the impact of the foreign direct investments to Turkey’s economic growth which ones come to Turkey during 2003-2013 periods. Data’s were obtained from the websites of official institutions of related organizations that includes 2003-2013 periods. The relationship between foreign direct investment and economic growth was tested by using Granger causality analyzes. In conclusion, in 2003-2013 periods, there has been no significant causal relationship between economic growth and foreign direct investment in Turkey.